Степан Олексюк (Тудор) як представник Львівської філософської школи: аналіз юмівського поняття перцепції - Іваник, Степан (Видавництво Національного університету "Львівська політехніка", 2009)
The main idea of thesis is to present a philosophic creation of Stepan Oleksiuk – the one of Ukrainian representatives of Lvov philosophic school.
Keywords: perception; analytical method; Lvov-Warsaw philosophic school